Evaluación in vitro de la capacidad bacteriana para remover plomo en aguas residuales sintéticas - Guerra Guevara, Santiago Paúl (2016)
In this study it has been performed an in vitro characterization of 152 strains and microbial consortia, in order to mitigate the environmental impacts of different industrial activities related to mining, petrochemical and metallurgical sector. In isolation and biostimulation phase, bacteria were put through a selection in modified crop, in which 20 and 100 ppm lead concentrate was added, finally obtaining five strains that were shown to be resistant and/or tolerant to Pb. Determination of bacterial removal capacity of lead was experienced under two conditions: incubation at controlled temperature of 25˚C and incubation at room temperature (between 5°C and 23°C for the southern area of Quito in the months of study). The biochemical characterization of bacteria was performed using Microgen GN-ID A + B System, identifying the following genera: Acinetobacter, Pseudomonas, Aeromona and species: Aeromona hydrophila and Photobacterium damselae, it which obtained a percentage of 99.8% of certainty. During the elaboration of the curves of kinetic bacterial growth and Pb remotion, turbidimetry and atomic absorption techniques were used, where Aeromona hydrophila showed a greater ease of growth at a 20 ppm concentration in incubation at room temperature, while Pseudomona sp registered a total removal percentage of 96.30% with a 100 ppm concentration and room temperature incubation. This research is intended as a guide for future studies, so that it can be used as an alternative for more efficient and cheaper remediation regarding conventional remediation technologies.